2011
DOI: 10.17656/jsmc.10011
|View full text |Cite
|
Sign up to set email alerts
|

Oral Findings and Microflora in Type Ii Diabetes Mellitus in Sulaimani City

Abstract: Background  The effects of diabetes mellitus on human include long term dysfunction and failure of various organs. A number of oral diseases and disorders have been associated with diabetes mellitus. The susceptibility to periodontal disease often called the "sixth complication of diabetes mellitus" is the most common oral complication of diabetes. The oral cavity is comprised of many surfaces, each coated with a plethora of different bacteria, some of which have been implicated in oral diseases such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
2
6
1
Order By: Relevance
“…In this study, type 2 diabetic patients have significantly higher periodontal disease parameters including: gingival index, probing pocket depth, and clinical attachment level than healthy controls. This finding is in line with other studies which proved and confirmed that type 2 diabetes mellitus has been unequivocally considered as a major risk factor for periodontitis and the risk of progressive periodontal destruction in subjects with diabetes has been demonstrated in many studies in comparison with controls (3)(4)(5)(6) . In contrast to above findings only few reports showed either no relation or weak significant relation between periodontal disease and type 2 diabetes (17,18) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, type 2 diabetic patients have significantly higher periodontal disease parameters including: gingival index, probing pocket depth, and clinical attachment level than healthy controls. This finding is in line with other studies which proved and confirmed that type 2 diabetes mellitus has been unequivocally considered as a major risk factor for periodontitis and the risk of progressive periodontal destruction in subjects with diabetes has been demonstrated in many studies in comparison with controls (3)(4)(5)(6) . In contrast to above findings only few reports showed either no relation or weak significant relation between periodontal disease and type 2 diabetes (17,18) .…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have suggested a link between type 2 diabetes mellitus and increased risk of progressive periodontal destruction (3)(4)(5)(6) . On the other hand, other studies reported an association between periodontal disease and cardiovascular disease and found a significant higher incidence of cardiovascular disease in subjects with periodontal disease compared to subjects without periodontal disease, or in subjects with more severe periodontitis compared to subjects with less severe periodontitis (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…The carriage affected by ethnic group (44) , family predisposition (45) . Carriage rates are also higher in individuals with insulin-dependent diabetes, in patients on continuous ambulatory peritoneal dialysis and haemodialysis and in intravenous drug abusers when compared with the healthy population (26) or from the oral cavity of patient with type II diabetes mellitus compared with healthy not diabetics (6) . Our figures of carriage (18%) among health worker fall in this range and also showed more carrier tendency to S. aureus and S. epidermidis as other studies showed (37) .…”
Section: Discussionmentioning
confidence: 99%
“…Testing the response of S. aureus to other agents showed multi resistant nature of S. aureus. In a local study of oral flora in type II diabetes mellitus, the antimicrobial susceptibly of 31 oral isolates of S. aureus showed multiple resistance against many antimicrobials used to treat oral infections (6) . In the current study , choosing such antibacterial agent was based on reasons, still our local practice of antimicrobial treatment goes with giving agents such Amoxicillin/Calvulinic or Oxacillin to many suspected staphylococcal infections while Fusidic acid and Vancomycin were selected due to many resistance reports to these powerful antimicrobial agent which was conserved to treat staphylococcal infection (3,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation